2013
DOI: 10.1037/a0029672
|View full text |Cite
|
Sign up to set email alerts
|

Professional psychology in Canada: A survey of demographic and practice characteristics.

Abstract: The number of psychological practitioners in Canada has grown substantially over the past two decades, and numerous professional and legislative changes have occurred during this time. However, the most recent surveys examining the nature of professional psychology in Canada were published more than 20 years ago. To obtain current information on the practice of professional psychology, 538 practitioners completed a survey focusing on demographics and practice characteristics. Among other general practice findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 13 publications
4
39
0
4
Order By: Relevance
“…These trends are impressive given that Quebec, as a number of jurisdictions of the country, moved from a master's to a doctoral degree requirement in 2001. The rising number of Canadian clinicians could reflect, amongst other things, the multiplication of accredited programs (Hunsley et al., ). Quebec's greater growth could possibly be explained by lower educational costs and greater accessibility of graduate studies in psychology, as in other disciplines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These trends are impressive given that Quebec, as a number of jurisdictions of the country, moved from a master's to a doctoral degree requirement in 2001. The rising number of Canadian clinicians could reflect, amongst other things, the multiplication of accredited programs (Hunsley et al., ). Quebec's greater growth could possibly be explained by lower educational costs and greater accessibility of graduate studies in psychology, as in other disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, research on the practice of clinical psychologists is limited, apart from Hunsley, Ronson, and Cohen's () recent work. Their study examines the practice and demographics of clinical psychologists through a survey (N = 538 in 2012).…”
mentioning
confidence: 99%
“…Unlike the United States, it has a long history of individuals with Masters degrees practicing with the title of "psychologist." In the past 30 years, some provinces have shifted from requiring a master's to a doctoral degree, and others have created the title of "psychological associate" for those with master's degrees (Hunsley, Ronson, & Cohen, 2013). Many provinces and territories also require the EPPP.…”
Section: Regulationmentioning
confidence: 99%
“…In a survey of Division 12 members, Norcross and Karpiak (2012) found that diagnosis and assessment, despite becoming less central in clinical psychology than in the past, remains the second most frequent professional activity among clinical psychologists, following psychotherapy, with just under 60% of their survey respondents reporting engagement in diagnosis/assessment. In a survey by Hunsley, Ronson, and Cohen (2013) of registered psychologists in Canada, assessment accounted for the respondents' second largest investment of professional time, following psychotherapy, and 83% of those with doctoral degrees reported engagement in assessing mood and behavior. Neimeyer, Taylor, and Wear (2010) asked over 6,000 licensed psychologists in an online survey about the topics of continuing education courses they had taken in the past year.…”
Section: Practice Activitiesmentioning
confidence: 99%